Dimethyl fumarate attenuates pain behaviors in osteoarthritis rats via induction of Nrf2-mediated mitochondrial biogenesis. (27th August 2022) - Gao, Shao-Jie; Li, Dan-Yang; Liu, Dai-Qiang; Sun, Jia; Zhang, Long-Qing; Wu, Jia-Yi; Song, Fan-He; Zhou, Ya-Qun; Mei, Wei
Osteoarthritis (OA), a chronic degenerative disease, leads to pain and loss of function. Existing treatments for OA pain have limited efficacy and show significant side effects. Dimethyl fumarate, a robust nuclear factor erythroid 2-related factor 2 (Nrf2) activator, could alleviate pain behaviors in chronic pain. This study aims to investigate the role of dimethyl fumarate in a rat model of OA induced by monosodium iodoacetate (MIA) and its underlying mechanisms. We used von Frey filaments to assess the mechanical allodynia. Weight-bearing apparatus was employed to assess the hindlimb weight distribution. Western blot was employed to investigate the protein expressions of mitochondrial biogenesis markers. RT-qPCR was employed to examine the copy number of mitochondrial DNA (mtDNA). In our study, dimethyl fumarate upregulated mechanical paw withdrawal threshold (MPWT) (MIA + Vehicle, 1.6 ± 0.13 g [mean ± SEM]; MIA + Dimethyl fumarate (DMF) 300 mg/kg, 10.5 ± 0.96 g ; p < 0.0001). Hindlimb weight distribution was also upregulated by dimethyl fumarate (MIA + Vehicle, 38.17 ± 0.72 g ; MIA + DMF 300 mg/kg, 43.59 ± 1.01 g ; p < 0.01). Besides, activation of Nrf2 remarkably upregulated the protein levels of PGC-1α (MIA + Vehicle, 0.69 ± 0.07; MIA + DMF 300 mg/kg, 1.08 ± 0.09; p = 0.0037), NRF1 (MIA + Vehicle, 0.69 ± 0.04; MIA + DMF 300 mg/kg, 1.00 ± 0.11; p = 0.0114), TFAM (MIA + Vehicle, 0.62 ± 0.11; MIA + DMF 300 mg/kg, 1.02 ± 0.12; p = 0.0147), and the copy number of mtDNA (MIA + Vehicle, 0.52 ± 0.05; MIA + DMF 300 mg/kg, 3.81 ± 0.21; p < 0.0001). Taken together, these results show that dimethyl fumarate alleviated pain-related behaviors in a rat model of OA through activation of Nrf2-induced mitochondrial biogenesis.